2020
DOI: 10.4037/ccn2020939
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Deprivation in the Intensive Care Patient

Abstract: Topic Sleep deprivation in the intensive care unit setting. Clinical Relevance The Society of Critical Care Medicine has identified sleep deprivation as a significant contributor to the development of delirium in adult patients in the intensive care unit. Thus, preventing and managing sleep deprivation is important in reducing the incidence of delirium in this patient population. A multifaceted and multidisciplinary approach … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 47 publications
(138 reference statements)
1
16
0
Order By: Relevance
“…For non-pharmacological nursing interventions, wearing eye masks and earplugs are the most used care techniques to manage environmental factors (Grimm, 2020). However, 65.9% of nurses integrate complementary and alternative medicine (CAM) therapy, especially massage therapy (MT), in their patients' treatment to reduce patients' stress and anxiety and improve their health (Balouchi et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For non-pharmacological nursing interventions, wearing eye masks and earplugs are the most used care techniques to manage environmental factors (Grimm, 2020). However, 65.9% of nurses integrate complementary and alternative medicine (CAM) therapy, especially massage therapy (MT), in their patients' treatment to reduce patients' stress and anxiety and improve their health (Balouchi et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…To date, only three review studies and one meta‐analysis have examined the effects of MT on critically ill patients (Grimm, 2020; Jagan et al, 2019; Yari et al, 2021). Jagan et al (2019) found that massage interventions positively affect the outcomes of critically ill patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature, it was reported that patients in the ICU experienced sleep disorders at rates ranging from 24% to 90% (Al Mutair et al, 2020; Huang et al, 2014). Although the rates may vary from study to another, it has been stated that 75% of intensive care patients have sleep problems due to noise, alarm sounds are the leading cause of noise, and the most prominent complaints of patients about sleep are waking up frequently (Boesen et al, 2016; Demir & Öztunç, 2017; Grimm, 2020; Pulak & Jensen, 2016). These results show that there is a need for tools and equipment to reduce the exposure of patients to noise in the ICU.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is low adherence to these measures, and they need to be adequately incorporated into routine team practices. 14 , 16 …”
Section: Introductionmentioning
confidence: 99%